Legal Review of Knock-off Culture in K-Pop-Inspired Outfits Based on Industrial Design Law - Zahra, Fatimatuz; Suparnyo (Media Iuris, 2025)
Knock-off culture in K-Pop-inspired outfits is quite contrary to Indonesia’s objective in developing the industrial sector, which is increasing competitiveness through the optimization of industrial design that is rooted in Indonesia’s cultural wealth as a part of integrity in global trading. Considering the increasing number of local brands that replicate the industrial designs of foreign brands to fulfill consumer demands, it is crucial to study the knock-off culture phenomenon in local brands of fashion inspired by K-pop idols from the perspective of Law Number 31 of 2000 concerning Industrial Design (Industrial Design Law). This research is conducted using the normative juridical method which is strengthened by the socio-legal approach related to the knock-off culture’s progress in society. This research results indicate that provisions in Industrial Design Law are still ambiguous, especially those related to the principle of novelty and ambiguity regarding the knock-off products that haven’t been arranged clearly. Those indicate the lack of adequate legal apparatus that potentially triggers unfair business competition, and also increases the risk of violating intellectual property rights.